Do Surgeons Treat Their Patients Like They Would Treat Themselves? - Stein J. Janssen; Teun Teunis; Thierry G. Guitton; David Ring (2015)
There is substantial unexplained geographical and surgeon-to-surgeon variation in rates of surgery. One would expect surgeons to treat patients and themselves similarly based on best evidence and accounting for patient preferences.(1) Are surgeons more likely to recommend surgery when choosing for a patient than for themselves? (2) Are surgeons less confident in deciding for patients than for themselves?Two hundred fifty-four (32%) of 790 Science of Variation Group (SOVG) members reviewed 21 fictional upper extremity cases (eg, distal radius fracture, De Quervain tendinopathy) for which surgery is optional answering two questions: (1) What treatment would you choose/recommend: operative or nonoperative? (2) On a scale from 0 to 10, how confident are you about this decision? Confidence is the degree that one believes that his or her decision is the right one (ie, most appropriate). Participants were orthopaedic, trauma, and plastic surgeons, all with an interest in treating upper extremity conditions. Half of the participants were randomized to choose for themselves if they had this injury or illness. The other half was randomized to make treatment recommendations for a patient of their age and gender. For the choice of operative or nonoperative, the overall recommendation for treatment was expressed as a surgery score per surgeon by dividing the number of cases they would operate on by the total number of cases (n = 21), where 100% is when every surgeon recommended surgery for every case. For confidence, we calculated the mean confidence for all 21 cases per surgeon; overall score ranges from 0 to 10 with a higher score indicating more confidence in the decision for treatment.Surgeons were more likely to recommend surgery for a patient (44.2% ± 14.0%) than they were to choose surgery for themselves (38.5% ± 15.4%) with a mean difference of 6% (95% confidence interval [CI], 2.1%-9.4%; p = 0.002). Surgeons were more confident in deciding for themselves than they were for a patient of similar age and gender (self: 7.9 ± 1.0, patient: 7.5 ± 1.2, mean difference: 0.35 [CI, 0.075-0.62], p = 0.012).Surgeons are slightly more likely to recommend surgery for a patient than they are to choose surgery for themselves and they choose for themselves with a little more confidence. Different perspectives, preferences, circumstantial information, and cognitive biases might explain the observed differences. This emphasizes the importance of (1) understanding patients' preferences and their considerations for treatment; (2) being aware that surgeons and patients might weigh various factors differently; (3) giving patients more autonomy by letting them balance risks and benefits themselves (ie, shared decision-making); and (4) assessing how dispassionate evidence-based decision aids help inform the patient and influences their decisional conflict.Level III, diagnostic study.